Balanced Scorecard no Instituto Nacional do Seguro Social: uma análise segundo a percepção dos servidores da linha de frente - Bergenthal, Vanessa Grasiela (2012)
Strategic planning is a management tool consolidated and embraced by both private and public organizations. One of the most widely used models in this sense is the Balanced Scorecard. It happens that the use of this model in public organizations requires more attention and adaptations, since one of its four perspectives (financial) loses importance. Furthermore, studies show that to succeed, the Balanced Scorecard must be disclosed and understood by all members of the organization, especially by the servants that actuate at the operational level, who understand the dynamics and peculiarities of the daily work and could suggest important procedures improvements. The INSS uses the Balanced Scorecard as a strategic management model, outlining a strategy map for the period 2009-2015. This study aimed to verify if the tool adopted is known and understood by frontline servants. To this end, questionnaires and interviews were applied to the servants that operate at the INSS's Executive Management frontline in Santa Maria-RS, aiming to collect and analyze such perceptions. The result shows that these servants evaluate the Balance Scorecard positively, but points out some problems and suggestions that can support the decisions making process of the INSS's senior administration.